Enablers and Obstacles in Integrated Water Resources Management (IWRM) Implementation and Their Contributions to Sustainable Territorial Development - Gallegos Monteagudo, Armando (2026)
Advancing Integrated Water Resources Management (IWRM) is essential for integrating land and water strategies and ensuring access to safe and secure water services. Yet, assessing the quality of IWRM implementation remains a persistent challenge for policy and practice. This study presents the first systematic review of 375 empirical articles to consolidate evidence on how enablers and obstacles shape IWRM’s effectiveness in advancing Sustainable Territorial Development (S-TD). Following PRISMA guidelines and combining bibliometric and qualitative coding procedures, we identify ten categories of enablers and eleven categories of obstacles. Results show that institutional strengthening, stakeholder participation, and technological innovation are the most frequent enablers, while fragmentation, coordination challenges, and financial limitations are the most prevalent obstacles. Beyond frequency patterns, this review highlights that outcomes depend on the configurations and interactions of these factors, which condition IWRM’s capacity to steer sustainable development trajectories in the territory. By comparing enablers and obstacles across nexus sectors (food, energy, land) and geographic scales (sub-basin, basin, transboundary, urban, national), we delineate scale- and sector-sensitive pathways linking IWRM to S-TD. To support further research, we provide an open-access dataset as a unique resource for replication, comparative analysis, and policy design, enabling evidence-based decision-making toward sustainability and resilience across diverse geographical and institutional contexts.